Pengaruh Intellectual Capital dan Profitabilitas terhadap Firm Value (Studi pada Perusahaan Manfaktur Sub-Sektor Food & Beverage yang Terdaftar di BEI Periode 2020-2023) - Fidela Salsabilla Maheswari; Fitra Dharma (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2025)
This study aims to analyze the effect of intellectual capital and profitability on firm value in manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange (IDX) during the 2020-2023 period. Intellectual capital is measured using the Value Added Intellectual Coefficient (VAIC) method, which consists of three components: Value Added Capital Employed (VACA), Value Added Human Capital (VAHU), and Structural Capital Value Added (STVA). Meanwhile, profitability is proxied by Return on Assets (ROA). This study uses a quantitative approach with purposive sampling, resulting in 59 companies as research samples. After data screening and the removal of outliers, the number of observations analyzed was 138. The data were analyzed using multiple linear regression with SPSS software. The results of the study show that intellectual capital does not have a significant effect on firm value. This finding indicates that the management and disclosure of intellectual assets in food and beverage companies have not been able to improve investors' perception of the company’s market value. On the other hand, profitability has a positive and significant effect on firm value. This means that the higher the profitability, the higher the firm value, as reflected in investor confidence. This study emphasizes that conventional financial indicators remain the main focus of investors, while the role of intellectual capital has not yet been fully considered as a strategic resource that can directly enhance firm value.